Equality and Equity in Indonesian Education: The Consequences of Decentralization - Venny Karolina; Sri Buwono; Aminuyati Aminuyati; Hadi Wiyono; Carla Queiroz (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
This paper discussed Indonesian efforts to change the Indonesian educational system from centralization to decentralization. The Indonesian government launched several programmes to support its decentralization policy in education. The programmes were intended to open equal access to education all over Indonesia and minimize the gap among the regions. This paper analysed whether the programmes provided equality and equity to Indonesian citizens in terms of educational access. Finally, this researcher recommended that the Indonesian government gives more attention to the disadvantaged area, for example, poor and remote regions. This may provide equal access to education with good quality in Indonesia. Moreover, the Indonesian central government may allow local authorities to get involved in teacher professionalism programmes. Local authorities may invite successful educators from other regions to learn their successful localized curriculum. Finally, the central government must ensure that local government apply a minimum of 20% of its budgets for education. The funding might help local educational authorities pay teachers' salaries on time as the delay in teacher salaries may affect negatively their work conditions.